2011
DOI: 10.4103/0970-2113.85687
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of tuberculosis in HIV/AIDS patients and its relationship with CD4 count

Abstract: Background:HIV/AIDS pandemic is responsible for the resurgence of TB worldwide, resulting in increased morbidity and mortality. HIV and Mycobacterium tuberculosis have a synergistic interaction; each propagates progression of the other. Coinfection with HIV infection leads to difficulties in both the diagnosis and treatment of tuberculosis, increase risk of death, treatment failure and relapse.Objective:The aim of the present study is to study the clinical, radiological profile of pulmonary and extrapulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 7 publications
(6 reference statements)
3
16
1
Order By: Relevance
“…Previously, age was reported as an independent risk factor for EPTB infection in high-burden countries [26,32,33]. This is consistent with other studies in San Francisco, Saudi Arabia, India and Tanzania which showed that high prevalence of EPTB among productive age groups [26,28,30,34]. Most of tuberculosis cases in this population might be largely related to ongoing tuberculosis transmission, given that the associated age group (31–40 years) is known as the most unstable and high risk group for TB transmission.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previously, age was reported as an independent risk factor for EPTB infection in high-burden countries [26,32,33]. This is consistent with other studies in San Francisco, Saudi Arabia, India and Tanzania which showed that high prevalence of EPTB among productive age groups [26,28,30,34]. Most of tuberculosis cases in this population might be largely related to ongoing tuberculosis transmission, given that the associated age group (31–40 years) is known as the most unstable and high risk group for TB transmission.…”
Section: Discussionsupporting
confidence: 87%
“…Male patients were more likely to present with extra pulmonary tuberculosis than females (58.8% versus 41.2%). This is supported by other reports from India, (65.6% versus 34.4%), Malatya/Turkey, (53.4% versus 46.6%) and Nigeria, (64.6 % versus 35.4%) [21,28,29]. However, there are contradictory reports on the EPTB prevalence among male and female patients.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies also reported results of severe immune suppression with median CD4 count reaching sixteen to fourteen [7,23,39]. This finding contrasts a previous study conducted by Kingkaew et al, which founded that 71, 8% of HIV infected patients with TBM had CD4 lymphocyte counts < 100 [40]. Anti-TB treatment should be started once TBM is suspected because of the associated high case fatality [3,7].…”
Section: Issn: 2373-8995contrasting
confidence: 56%
“…Higher rates of mortality have been described in other study conducted in Cameroon. Studies from Brazil and China reported rates of mortality at 29% [40]. In HIV infected patients, a lower CD4 cell counts [3,23], focal signs and altered consciousness on admission, were found to be a factor associated with poor prognosis [47].…”
Section: Issn: 2373-8995mentioning
confidence: 99%
“…[4,5] Therefore, the HIV/AIDS pandemic is responsible for the resurgence of TB worldwide, resulting in increased morbidity and mortality. [6,7] Even in antiretroviral (ART) treated patients, TB is the most common presenting illness. [8,9] HIV infected patients on HAART have a tuberculosis incidence rate of 5.4 cases/100 person-years, approximately 10-15 times higher than tuberculosis incidence rates in HIV-negative patients in the same community.…”
Section: Introductionmentioning
confidence: 99%